Typomorphism of rock-forming minerals of Lunar regolith, Luna-16, -20, -24: comparision of sea vs continent vs sea - A. B. Makeyev; N. I. Bryanchaninova (Georesursy, 2024)
The study focuses on the comparison of the chemical and mineral composition of Lunar regolith probes from Luna-16, -20, -24 stations and their the seacontinent environments. Using microprobe JXA-8200 and JSM-5610LV (400 analyses, 50 images, 9 fragments of layer-by-layer core samples) 18 mineral phases and their 12 varieties were diagnosed. The most common are ironmagnesium and calcium-bearing varieties of silicates – anortite, clinopyroxenes and olivine. The typomorphic features of rock-forming minerals in two types of the lunar surface are discussed. The composition of chromespinelids is demonstrated on a triangular prism diagram.